2019
DOI: 10.1080/23744235.2019.1637536
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the switch of Triumeq® to generic (abacavir + lamivudine) + Tivicay®: data at 48 weeks

Abstract: Background: Generic drugs may help to support antiretroviral treatment. We want to assess the efficacy and safety at 24 weeks of the change of coformulated (abacavir + lamivudine + dolutegravir) to (abacavir + lamivudine) coformulated as a generic pharmaceutical specialty + dolutegravir. Methods: Between February and June 2017, switch from Triumeq® to a generic pharmaceutical specialty co-formulated tablet (abacavir + lamivudine) plus Tivicay® was made. Demographic, viroimmunological characteristics and the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The relatively low rate of generic prescriptions (30.2%) in our study could be first explained because of the two levels of legal protection in France: intellectual property protection of the patent, which protects commercial exploitation for a period of 20 years, and administrative protection, as any drug is protected for a period of 8 years from the date of the first marketing authorization, thus favoring branded STR prescriptions. The second explanation could be the unwillingness of French medical doctors to de-simplify a branded STR regimen, which has been shown to be accepted by half of the people [9–11], with similar virologic outcomes to branded STR [12–14]. In 2015, a French study showed that up to 26% of prescribers favored de-simplifying STR to promote generic drugs [15].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low rate of generic prescriptions (30.2%) in our study could be first explained because of the two levels of legal protection in France: intellectual property protection of the patent, which protects commercial exploitation for a period of 20 years, and administrative protection, as any drug is protected for a period of 8 years from the date of the first marketing authorization, thus favoring branded STR prescriptions. The second explanation could be the unwillingness of French medical doctors to de-simplify a branded STR regimen, which has been shown to be accepted by half of the people [9–11], with similar virologic outcomes to branded STR [12–14]. In 2015, a French study showed that up to 26% of prescribers favored de-simplifying STR to promote generic drugs [15].…”
Section: Discussionmentioning
confidence: 99%